CRITICAL ANALYSIS OF INVESTOR EDUCATION PROGRAMS IN INDIA'S CAPITAL MARKET: FOCUS ON SEBI - Hayat, Mohsina (Jurnal Ilmu Ekonomi dan Pembangunan, 2024)
The study aims to assess the effectiveness of these programs in enhancing investor awareness, confidence, and participation in the capital market. Utilizing a mixed-methods approach, including surveys, interviews, and analysis of secondary data, the research evaluates the strategies employed by SEBI, examines regulatory challenges, and measures the impact of these programs on investor behavior. The findings indicate that SEBI's initiatives have significantly improved investor knowledge and engagement, but there remain gaps in reaching rural and less-educated segments. The study also identifies areas for improvement, such as incorporating more digital tools and personalized educational content to keep pace with the rapidly evolving market landscape. These results provide valuable insights for policymakers, regulators, and educators to enhance the scope and effectiveness of investor education in India. By empowering investors with essential knowledge, these programs contribute to market integrity, financial inclusion, and the overall stability of the Indian capital market. Continuous monitoring, stakeholder feedback, and adaptive strategies are essential to maintaining the relevance and impact of investor education initiatives.